Lokal Wisdom as a Disaster Mitigation Strategy “Experiences of Coastal Communities in South Bantul” - Suryani (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study explores local wisdom as an effective and sustainable disaster mitigation strategy, reflecting generational knowledge, cultural values, and communal practices in response to natural threats. Focused on the disaster-prone Bantul region in Yogyakarta, the research employs a descriptive qualitative method, gathering data through in-depth interviews, documentary studies, and extensive field observations. The analysis examines how indigenous perspectives provide a foundation for long-term safety and environmental harmony. Results indicate that local wisdom, driven by the spirit of mutual cooperation (gotong royong), significantly facilitates disaster preparedness and emergency management. Integrating these traditional practices with modern technology creates a more inclusive and robust mitigation system. A primary finding emphasizes the necessity of community involvement; local residents utilize traditional early warning systems-such as nature-based indicators-uniquely adapted to their specific geography. This localized approach effectively reduces risks in highly vulnerable areas, including coastal zones, mountain slopes, and flood-prone regions. Ultimately, leveraging local wisdom enhances community resilience and preserves cultural heritage against the modern pressures of climate change and rapid urbanization. The study recommends strengthened, synergistic collaboration between central governments, local authorities, and grassroots communities to better manage sudden natural disasters and ensure a sustainable, safe future for all citizens.